Characteristic Features of Grabar Terms and Their Manifestations in Modern Eastern Armenian Term System - Abajyan, Anna (Bulletin of Yerevan University B: Philology, 2024)
The given study deals with the examination of the formation of Grabar terms and word-terms and their manifestations in the term system of Modern Armenian. The focus of the study is the basis through which a word becomes a term or a word-term form is examined. In the result of the research carried out we arrived at the conclusion that the following features contribute to the formation of terms and word-terms.1) Polysemy at the level of lexicology. Based on each of their meanings, words become a unit of a sub-structure representing any field or a micro-system;2) Homonymy, by which the given word forms various word-terms expressing that concept,3) Synonymy, conditioned by the fact that in the given sense a unit of each sub-layer is polysemantic also as a term or a word term. This is an inextricably interlinked chain, each component of which has a lexical meaning, a term meaning based on the given lexical meaning, demonstrates polysemancy based on the part of speech basis, has a stylistic value by which the linguistic stylistic features and peculiarities of the chronicler's pen are added to the features mentioned above. Grabar word-forms and terms have become the key basis on which the term system of Modern Eastern Armenian was formed, developed and continues to develop.
Keywords: word-term; term; polysemy; homonymy; synonymy; polysemancy; part-of-speech; meaning; stylistic value; Grabar; Eastern Armenian